A71 INFORMED CONSENT AND BOOKING METHOD IN COLONOSCOPY. (1st March 2018) - Morrison, J B; Harding, A; Williams, S
Abstract: Background: Within the Nova Scotia Health Authority, patients are booked for colonoscopy via various routes. Many are seen for consultation in clinic and the informed consent discussion is held with their physician. Patients are also booked directly for colonoscopy ("direct access") based on information provided in the original referral without having been seen by their physician. Recently, a third route to booking has been introduced which involves consultation in person or via telephone with a registered nurse as part of the Nova Scotia Provincial Colon Cancer Screening Program. This evaluation includes education about the procedure and the bowel preparation. There have been concerns raised as to whether patients booked via direct access have an adequate level of pre-procedural education and are able to provide true informed consent. It is not clear whether patients who have had a pre-procedural consultation with either a physician or nurse are better equipped to provide informed consent compared to those booked direct to procedure. Aims: This study aims to evaluate the levels of informed consent for colonoscopy patients depending on the method by which they were booked for their scope. Methods: This study is questionnaire-based with surveys being administered to colonoscopy patients at two sites within the NSHA. Surveys are provided to all patients seen for outpatient colonoscopy outside the context of a clinical trial. Patients who have had previous colonoscopy were excluded. The questionnaire was validated based on the input of several health care practitioners and feedback from patients. Results: To date, there have been 17 responses from the pilot study, and 29 responses to the finalized version. Of these, 18 responses were first-time colonoscopy patients and therefore relevant to this study. Data acquisition is ongoing. Thus far, 6 patients (33.3%) were booked after seeing a physician, 7 patients (38.9%) after being screened by a nurse, and 5 (27.8%) were booked direct to procedure. All patients reported being either satisfied (61.1%) or very satisfied (38.9%) with their level of understanding prior to their procedure. All patients stated that they understood the benefits and risks of colonoscopy prior to their procedure. All patients stated that they felt adequately prepared about what was happening to them. Conclusions: his pilot project confirms that patient satisfaction levels with the pre-procedural education they receive before colonoscopy are high. Greater numbers of survey responses will help determine if there are subtle differences in patient satisfaction dependent on the method of booking. This study implies that nurse-driven pre-screening results in similar patient satisfaction levels as the traditional approaches to booking. Funding Agencies: None